(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Foreign language as one of the means of communication occupies a special place in the system of modern higher education. The article deals with the problem of communicative foreign competence formation among students of technical specialties. The author determines the teaching of a foreign language as a special kind of speech activity, based on a clearly organized system of educational speech actions. In this article, this system is presented in the form of teaching English texts reading, which requires the use of special speech material and an exercise system for performing this type of activity. The author presented the system of exercises with the purpose of forming of students’ communicative competence.